Profile analysis through self-determination theory and intention to be physically active: differences according to gender and age - Manzano-Sánchez, David (Frontiers in Psychology, 2023)
Physical Education in the current educational system, has different objectives, within these, we find to educate in values and increase the physical activity levels of students. For this, the objective of the present study was to analyze the motivational profiles of students, to know which profiles approached higher levels of responsibility, satisfaction of the autonomy, competence and social relationship needs, intention to be physically active and perception of autonomy support. A total of 752 students from Primary, Secondary and Non-compulsory education (M = 13.809; SD = 1.984, 47.9% boys and 52.1% girls), from different educational centers in Spain, participated in the study, to whom a series of questionnaires were administered to find out their values of the mentioned variables. The results established the existence of four profiles called "high quality", "low quality", "high quantity" and "low quantity" of motivation. The results reflected that the students of the "high quality" and "high quantity" profiles had higher values in all the variables in relation to the other two groups (except in amotivation and external regulation), discussing the differential analysis between the four groups. The group with the best results being that of "high quantity" as opposed to "low quantity". In turn, no differences were found according to gender, but according to the educational stage, Primary Education stage was more related to the more self-determined profiles. Therefore, it is necessary to look for more self-determined motivational profiles from an early age in order to improve levels of responsibility, the perception of autonomy, the satisfaction of basic psychological needs and the intention to be physically active.